Adorno, Habermas, and the search for a rational society - Cook, Deborah (Routledge studies in social and political thought, 2004)
Exploring the premises shared by Adorno & Habermas, along with their disagreements about social conditions today, this book defends Adorno against Habermas' criticisms. It is written for researchers & students of critical theory, political theory & the works of both scholars.